Analyzing EDFA Performance using different Pumping Techniques - Payal; Sharma, D; Kumar, S (International Journal of Computer Sciences and Engineering, 2025)
Wavelength Division Multiplexing (WDM) technology utilizes a multiplexer at the transmitter end and a demultiplexer at the receiver end to split the channels apart. Utilization of Erbium Doped Fiber Amplifier (EDFA) enables us to minimize various problems like insertion loss and dispersion. The EDFA-WDM System performance mainly depends on pumping technique used. We have analyzed various pumping techniques for a WDM system with pump powers from 40-120mW over different lengths of Erbium doped fiber (EDF). The designed system is analyzed in terms of Q-Factor and received power for a wavelength ranging 1530nm-1550nm with 0.5nm spacing. The results of pumping techniques are compared qualitatively to find the efficient performance of EDFA-WDM system.